2017
DOI: 10.1093/heapol/czx146
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to high and low performance: factors differentiating primary care facilities under performance-based financing in Nigeria

Abstract: The determinants of primary health facility performance in developing countries have not been well studied. One of the most under-researched areas is health facility management. This study investigated health facilities under the pilot performance-based financing (PBF) scheme in Nigeria, and aimed to understand which factors differentiated primary health care centres (PHCCs) which had performed well, vs those which had not, with a focus on health facility management practices. We used a multiple case study whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 32 publications
3
67
0
1
Order By: Relevance
“…By presenting itself as a comprehensive approach that makes it possible to address all aspects of the health system in any context, PBF monopolises attention and focuses policy dialogue on the short-term results of PBF programmes while diverting attention and resources from broader processes of change and necessary reforms. 53 We argue that the latter include a wide range of improvements to: working conditions; human resources management (disparities in health staff distribution; quality of initial and vocational training; low salaries and poor accountability; plethora of untrained health staff, as in the case of DRC) 64 ; transparency in use of financial resources; quality of care; integration of programmes and their monitoring and evaluation 65 ; accountability; performance of public financial management; engagement of communities (eg, as village health committees, traditional leaders and other community members) in governing the demand and supply of health services 66 ; and so on. Paradoxically, all of these are structural determinants of PBF’s own performance.…”
Section: Pbf May Actually Weaken Health Systemsmentioning
confidence: 99%
“…By presenting itself as a comprehensive approach that makes it possible to address all aspects of the health system in any context, PBF monopolises attention and focuses policy dialogue on the short-term results of PBF programmes while diverting attention and resources from broader processes of change and necessary reforms. 53 We argue that the latter include a wide range of improvements to: working conditions; human resources management (disparities in health staff distribution; quality of initial and vocational training; low salaries and poor accountability; plethora of untrained health staff, as in the case of DRC) 64 ; transparency in use of financial resources; quality of care; integration of programmes and their monitoring and evaluation 65 ; accountability; performance of public financial management; engagement of communities (eg, as village health committees, traditional leaders and other community members) in governing the demand and supply of health services 66 ; and so on. Paradoxically, all of these are structural determinants of PBF’s own performance.…”
Section: Pbf May Actually Weaken Health Systemsmentioning
confidence: 99%
“…This resonates findings from another process evaluation of the PBF intervention in Burkina Faso 40 and previous findings for instance in Malawi 8 or Nigeria. 42 Clearly, in a setting with severe human resources shortages like Burkina Faso, appointing only managers with sufficient managerial skill is not a viable option for sheer lack of qualified candidates to choose from. However, future training measures both within the context of PBF and beyond might want to focus more on training managers not only in technical but also in interpersonal aspects of organizational change processes.…”
Section: Discussionmentioning
confidence: 99%
“…Among many factors that potentially determine the performance of primary health facilities, one of the most under-researched areas is health facility management. Several studies [1][2][3][4][5] have identified specific health facility management practices that are associated with the improvement of health facility performance including: (i) engaging and problem-solving with local stakeholders [3], particularly with community leaders [5]; (ii) building a system of accountability [4], through performance management activities [5]; (iii) motivating health workers for change [2,3,5];…”
Section: Introductionmentioning
confidence: 99%
“…(iv) building work around teams and creating a sense of belonging, trust and respect [1,3,5]; (v) providing management support [1,3,5]; and (vi) improving health facility managers leadership competency to build a supportive environment for staff [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation